Trustworthy Global Computing 7th International Symposium, TGC 2012, Newcastle upon Tyne, UK, September 7-8, 2012, Revised Selected Papers - Palamidessi, Catuscia; Ryan, Mark D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Symposium on Trustworthy Global Computing, TGC 2012, held in Newcastle upon Tyne, UK, in September 2012. The 9 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 14 submissions. The papers cover a wide range of topics in the area of global computing and reliable computation in the so-called global computers, i.e., those computational abstractions emerging in large-scale infrastructures such as service-oriented architectures, autonomic systems and cloud computing, providing frameworks, tools, algorithms and protocols for designing open-ended, large-scale applications and for reasoning about their behavior and properties in a rigorous way.
From Rational Number Reconstruction to Set Reconciliation and File Synchronization -- Affine Refinement Types for Authentication and Authorization -- Seamless Distributed Computing from the Geometry of Interaction -- A Beginner$1 (Bs Guide to the DeadLock Analysis Model -- Formal Modeling and Reasoning about the Android Security Framework -- A Type System for Flexible Role Assignment in Multiparty Communicating Systems -- A Multiparty Multi-session Logic -- LTS Semantics for Compensation-Based Processes -- Linking Unlinkability -- Towards Quantitative Analysis of Opacity -- An Algebra for Symbolic Diffie-Hellman Protocol Analysis -- Security Analysis in Probabilistic Distributed Protocols via Bounded Reachability -- Modular Reasoning about Differential Privacy in a Probabilistic Process Calculus.s
Keywords: Computer science; Computer communication systems; Software engineering; Data encryption (Computer science).; Coding theory; Algorithms; Management information systems; Computer Science; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Software Engineering; Coding and Information Theory; Electronic books